Do Higher Wages Reduce Knowledge Worker's Job Mobility? Evidence for Swedish Inventors. (17th November 2017) - Ejermo, Olof; Schubert, Torben
Abstract: Based on linked employer‐employee panel data on all Swedish inventors, this paper analyses how wages affect inventors' job mobility. It is commonly assumed that higher wages reduce mobility because they reduce the value of outside opportunities. We argue that higher wages also send performance signals to potential employers, who raise their wage offers in response. By disentangling the effects of higher wages, we show evidence of a utility and an opportunity cost effect, which reduce mobility, and a performance‐signalling effect, which increases mobility. In our data, the effects cancel each other out, with no effects of wages on mobility rates on average. We find, however, that for star inventors, who have sufficiently strong alternative performance signals (e.g., strong patent records), the performance signal sent by wages is crowded out by the alternative signals. Accordingly, for star inventors we find that higher wages decrease mobility.